Fraction Subtraction

Easy

Medium

Difficult

Q1) \(\frac{6}{7}\) - \(\frac{5}{6}\) =
Q1) \(\frac{2}{3}\) - \(\frac{2}{15}\) =
Q1) 5\(\frac{1}{2}\) - 1\(\frac{8}{19}\) =
Q2) \(\frac{8}{9}\) - \(\frac{4}{5}\) =
Q2) \(\frac{5}{6}\) - \(\frac{1}{2}\) =
Q2) 2\(\frac{3}{4}\) - 1\(\frac{7}{9}\) =
Q3) \(\frac{2}{3}\) - \(\frac{3}{10}\) =
Q3) \(\frac{3}{4}\) - \(\frac{1}{5}\) =
Q3) 1\(\frac{2}{5}\) - 1\(\frac{2}{11}\) =
Q4) \(\frac{4}{7}\) - \(\frac{2}{7}\) =
Q4) \(\frac{3}{4}\) - \(\frac{5}{12}\) =
Q4) 3\(\frac{1}{3}\) - 1\(\frac{1}{9}\) =
Q5) \(\frac{2}{3}\) - \(\frac{1}{2}\) =
Q5) \(\frac{7}{10}\) - \(\frac{2}{3}\) =
Q5) 2\(\frac{1}{2}\) - 2\(\frac{1}{4}\) =
Q6) \(\frac{2}{3}\) - \(\frac{1}{2}\) =
Q6) \(\frac{3}{5}\) - \(\frac{2}{7}\) =
Q6) 3\(\frac{1}{2}\) - 1\(\frac{2}{5}\) =
Q7) \(\frac{2}{3}\) - \(\frac{2}{7}\) =
Q7) \(\frac{5}{6}\) - \(\frac{2}{3}\) =
Q7) 2\(\frac{2}{7}\) - 1\(\frac{3}{5}\) =
Q8) \(\frac{4}{5}\) - \(\frac{4}{9}\) =
Q8) \(\frac{9}{10}\) - \(\frac{3}{4}\) =
Q8) 5\(\frac{1}{2}\) - 1\(\frac{4}{13}\) =
Q9) \(\frac{4}{5}\) - \(\frac{2}{7}\) =
Q9) \(\frac{2}{3}\) - \(\frac{9}{14}\) =
Q9) 4\(\frac{1}{3}\) - 1\(\frac{7}{12}\) =
Q10) \(\frac{3}{5}\) - \(\frac{1}{2}\) =
Q10) \(\frac{6}{7}\) - \(\frac{5}{6}\) =
Q10) 2\(\frac{2}{3}\) - 1\(\frac{9}{13}\) =